Precision and accuracy of Dahl-Lea back-calculated smolt lengths from adult scales of Atlantic salmon (Salmo salar L.) - Hanson, Nora N; Smith, Gordon W; Middlemas, Stewart J; Todd, Christopher David (Journal of Fish Biology, 2019)
Using tagged and recaptured Atlantic salmon Salmo salar (n = 106) the present analysis shows that the most commonly applied linear back-calculation method for estimating past length, the Dahl-Lea method, resulted in overestimation of the length of large smolts and underestimation of small smolts. A correction equation (y = 0.53x + 6.23) for estimating true smolt length (y) from lengths back-calculated from adult scale measures (x) to account for these systematic discrepancies is proposed. Peer reviewed